Study on the Impact of Ventilation Methods on Droplet Nuclei Transmission in Subway Carriages - Xinkai Wu; Rui Ling; Xingyu Wan; Haihua Ren; Xuerun Jing; Guozeng Feng (Applied Sciences)
The environment inside subway carriages is relatively enclosed, putting passengers at risk of respiratory infections during viral pandemics such as COVID-19 and SARS. This paper uses the Euler–Lagrange method to simulate the distribution of droplet nuclei produced by coughing under six different operating conditions in a subway carriage. The study investigates the impact of different air supply characteristics and ventilation methods, including mixed ventilation (MV), floor-supply, and ceiling-return ventilation (SFRC), on the distribution of droplets. These results indicate that under MV mode, the dispersion range of droplets during a patient’s cough is the largest, with an average droplet suspension rate (SR) of up to 77% at the initial moment. The SFRC system markedly diminishes droplet dispersion, decreasing the SR by 35%. Upon increasing the air supply velocity to 0.8 m/s, the SR diminishes to 6%, the probability of particles attaining a 2 m social distance (PRP) declines by roughly 70%, and the weighted average contamination range (CR) of coughing particles reaching a safe social distance reduces by 33.5%. These results may act as a guide for the subsequent design and optimization of airflow patterns in carriages to reduce the risk of cross-infection.